Penerapan Asas Kepastian Hukum dalam Pemungutan Penerimaan Negara Bukan Pajak di Perusahaan Tambang Panas Bumi - Muhammad Alghifari Kusumawardany (Program Studi Ilmu Hukum, Universitas Kuningan, 2025)
The purpose of this study is to find out about the regulation of non-tax state revenue in geothermal mining companies and the implementation of the General Principles of Good Governance in the collection of Non-Tax State Revenue in geothermal mining companies. The method used in this study is normative juridical where the author collects literature sources and applicable laws and regulations. The results of this study are the regulation of non-tax state revenue regulated by Law Number 9 of 2018 concerning Non-Tax State Revenue which ensures and maintains the scope of non-tax revenue coverage, namely PNBP, so that it is in accordance with the package of Laws in the field of State Finance and also realizes good governance and there are still government officials who do not comply with the regulations with real evidence in the case study in the decision number: 90 / G / 2018 / PTUN-JKT that the official did not apply the principle of legal certainty in the collection of non-tax state revenue, thus causing losses for business actors. The conclusion of this study is that abundant natural resources, especially geothermal, can make a good contribution to the development of the country as long as the management is carried out by the state through instruments the government complies with applicable regulations.